Modelo de avaliação da sustentabilidade de pequenas propriedades rurais: uma abordagem multicritério linguística - Vian, Aleriane Zanetti (2020)
The sustainability guides society to generate sufficient resources for its maintenance, without compromising the resources for the future generations. Sustainability includes economic, social, and environmental aspects, the Triple Bottom Line. This scenario involves small rural properties, a source of production and development. These properties need to be economically viable and achieve sustainable practices, as society is increasingly seeking quality of life, healthy diet, environmental preservation, and economic and social development. With these premises, the objective of this study was to develop a model to assess the sustainability of small rural properties (MASPPR) through a multi-criteria linguistic model addressing the economic, social, and environmental dimensions. A systematic literature review was employed to select studies on the assessment of sustainability in rural properties. Based on the critical analysis of the literature, MASPPR structure is composed of the three sustainability dimensions, nineteen criterium groups, and fifty-eight criteria to assess the sustainability of small rural properties. MASPPR assesses sustainability based on a comparison of an assessment provided by regional experts. Appropriate research instruments obtain the information necessary for MASPPR, and the data is processed through 2-tuple linguistic operators, minimizing the loss of information. The results obtained with the MASPPR application were: In the property “A” the sustainability index of the Economic dimension was close to Reasonable (S3, 0.35), of the Social dimension close to High (S5, 0.40), Environmental dimension close to Reasonably High (S4, 0.13) with the Global Sustainability index of property “A” equal to (S4, 0.29). In the property “B” the sustainability index of the Economic dimension was close to Reasonably High (S4, 0.09), of the Social dimension close to Reasonably High (S4, 0.28), Environmental dimension close to Alto (S5, -0.09) with the Global Sustainability index of property “B” equal to (S4, 0.43). In the property “C” the sustainability index of the Economic dimension was close to Reasonably High (S4, -0.47), of the Social dimension close to Reasonably High (S4, 0.44), Environmental dimension close to High (S5, -0.27) with the Global Sustainability index of property “C” equal to (S4, 0,23). The three properties analyzed obtained a global sustainability index close to Reasonably High, with the difference in classification due to the preservation of information during the processing by the 2- tuple model. MASPPR is a structured and transparent model for rural producers and public managers to address sustainability for these properties and plan actions aiming sustainability.